Layanan Sirkulasi untuk Program Kampus Merdeka Sebagai Kesiapan Awal Implementasi Interlibrary Loan di Perpustakaan UNIKOM - Setiawati, Ubudiyah (Jurnal FPPTI, 2023)
The circulation service at the UNIKOM Library is a standard service for every library, namely providing services for accessing, reading and borrowing collections to take home. The Independent Campus Program, namely the 2nd Independent Student Exchange (PMM), gives students the opportunity to study at other universities outside the island where they live or where the university is located. The university you occupy must provide the same facilities, even if you only study for 1 (one) semester, in addition to the program set by the Merdeka Campus. Previous research mostly measured user perceptions or satisfaction from internal sources regarding circulation services. This research is to find out how the circulation service is for Merdeka Campus students who are students from other campuses. How many students utilize circulation service facilities (membership up, loan/return collection services and statistics). How do circulation services work according to 2nd PMM students? The method used is descriptive, quantitative. As a result, the UNIKOM Library has provided the same facilities, namely circulation services, to all Merdeka Campus students, who used 38.77% of visits (19 people) and borrowed 32.65% (16 people). The number of 2nd PMM students was 49 people, 19 of whom used the circulation service, this was based on the receipt of UNIKOM ID Cards after 2 months of college activities. This research shows that the use of circulation services for Merdeka Campus students is considered sufficient with a percentage above 30% or more than 15 people using UNIKOM Library facilities, the rest using other facilities from the PMM-MBKM program.